Synergistic agents for tumor-specific therapy mediated by focused ultrasound treatment. (19th November 2020) - Choi, Wonseok; Kim, Chulhong
Abstract : In this minireview, synergistic agents for focused ultrasound tumor treatment are reviewed in four therapy mechanisms: sonodynamic plus chemotherapy, microbubble-aided therapy, localized drug delivery, and photoacoustic image-guided therapy. Abstract : This minireview highlights the recent advances in the therapeutic agents that aim to provide synergistic enhancements of focused ultrasound treatment of tumors. Even though focused ultrasound therapy itself can bring therapeutic effects in cancers, many biochemical agents have been reported in the literature to enhance the treatment efficacy significantly. Until now, many mechanisms have been researched to advance the therapy, such as sonodynamic-plus-chemo-therapy, microbubble-aided therapy, localized release or delivery of nanomaterials, and multimodal image-guided therapy. Here, the novel materials adopted in each mechanism are briefly reviewed to provide a trend in the field and encourage future research towards the successful deployment of focused ultrasound therapy in real clinical environments.